INTERACTIVE POSSIBILITY OF WORKING WITH A DIGITAL VERSION OF THE JOURNAL "IZVESTIA OF THE CRAO" - Bondar’, N.; Gorbunov, M.; Shlyapnikov, A. (Одеські астрономічні публікації, 2013)
The main problem that arises when working with a scanned version of any published scientific journal related to the presentation of digital information displayed. In this paper, we consider the statistics, which represents the journal "Izvestia of the Crimean Astro- physical Observatory" in the SAO/NASA ADS. As the example of articles from the print version of the journal we consider the possibility to access the world’s astronomical databases for obtaining additional information about the investigated objects. We describe briefly on-line virtual applications for the graphical information display.